Honor among thieves - Caine, Rachel; Aguirre, Ann (Katherine Tegen Books, an imprint of HarperCollins Publishers, 2018)
Petty criminal Zara Cole is recruited into the Honors, an elite team of humans chosen by the Leviathan to explore the outer reaches of the universe.